Analysis of Children's Character Based on Parenting Patterns in Batuah Village - Siti Patimah; Sudarmono Sudarmono; Apuanor Apuanor (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to determine the influence of parenting patterns on children's character development in Batuah Village in 2025/2026. This study uses a qualitative approach with descriptive methods. The research subjects consisted of two 12-year-old children with the initials NLH and NRH, and one parent with the initials Mrs. M. The technique for data collection was carried out through structured in-depth interviews, while data analysis was carried out using the NVivo 12 application through the components Word Cloud and Word Tree to identify the relationship between parenting styles and children's character development. The results of the study indicate that the parenting style applied by parents tends towards permissive parenting, characterized by weak parental control, loose and free parenting, a lack of rules and boundaries, and excessive freedom. This condition is influenced by parents' busy work schedules, resulting in suboptimal supervision and guidance of children. In terms of character, children have demonstrated positive attitudes such as respecting elders and understanding the importance of trust. However, character development indicators such as emotions, habits, and desires have not developed optimally. Children still have difficulty controlling their emotions, exhibit aggressive behavior, have negative habits such as hitting and pitting friends against each other, and tend to follow their own desires. Nevertheless, children have understood the importance of trust and strive to repair relationships after making mistakes.